Heart failure and depression: A perspective from bibliometric analysis - Lam, Mei Ieng; Chen, Pan; Xie, Xiao-Meng; Lok, Grace K. I.; Liu, Yu-Fei; Si, Tong Leong; Ungvari, Gabor S.; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Background Depression commonly occurs in heart failure patients, and negatively influences quality of life and disease prognosis. This study explored heart failure and depression-related research from a bibliometric perspective. Methods Relevant publications were searched on June 24, 2022. The Bibliometrix package in R was used to conduct quantitative analyses including the trends in publications, and related countries, articles, authors and keywords. VOSviewer software was used to conduct the visualization map on co-word, co-author, and institution co-authorship analyses. CiteSpace software was used to illustrate the top keywords with citation burst. Results A total of 8,221 publications in the heart failure and depression-related research field were published between 1983 and 2022. In this field, the United States had the most publications (N = 3,013; 36.65%) and highest total citation (N = 149, 376), followed by China, Germany, Italy and Japan. Author Moser and Duke University were the most productive author and institution, respectively. Circulation is the most influential journal. Apart from “heart failure” and “depression,” “quality of life,” “mortality” and “myocardial infarction” were the most frequently used keywords in this research area; whereas more recently, “self care” and “anxiety” have been used more frequently. Conclusion This bibliometric analysis showed a rapid growth of research related to heart failure and depression from 1989 to 2021, which was mostly led by North America and Europe. Future directions in this research area include issues concerning self-care and anxiety about heart failure. As most of the existing literature were published in English, publications in other languages should be examined in the future.